Preparation method of amorphous iron core

Through pre-annealing, copper clad annealing and insulating adhesive impregnation, the problems of degradation of soft magnetic properties and increased high frequency loss of conventional amorphous iron cores are solved, and high permeability and low loss are achieved Amorphous iron core.

CN119446759APending Publication Date: 2025-02-14JIANGYIN JINGCI ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411463807.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The soft magnetic properties of conventional amorphous iron cores after annealing and after paint loss decrease, and the loss increases under high-frequency conditions, making it difficult to meet the demand for high-performance soft magnetic materials in modern electronic equipment.

Method used

A method of preparing an amorphous iron core is adopted, including pre-annealing treatment, secondary annealing treatment of inner and outer winding copper tape and vacuum impregnation of insulating adhesives, optimize the heat treatment process and enhance interlayer insulation to improve the amorphous iron core. Comprehensive performance.

Benefits of technology

The amorphous iron core prepared by this method exhibits good soft magnetic properties, the surface insulating layer is smooth and uncracked, the initial magnetic permeability is high, and the loss is low, so it can maintain excellent performance under high frequency conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of an amorphous iron core, and belongs to the technical field of amorphous iron cores. The invention discloses a preparation method of an amorphous iron core, which comprises the following preparation steps: (1) winding an iron-based amorphous alloy strip to obtain an amorphous iron core blank; (2) carrying out pre-annealing treatment on the amorphous iron core blank; (3) winding copper strips inside and outside the amorphous iron core blank subjected to pre-annealing treatment, and performing secondary annealing treatment; and (4) putting the amorphous iron core blank subjected to secondary annealing treatment into an insulating adhesive for vacuum impregnation, taking out the amorphous iron core blank, and putting the amorphous iron core blank into a drying oven for drying to obtain the amorphous iron core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of amorphous iron cores, and in particular to a method for preparing an amorphous iron core. Background Art Background Art

[0002] Amorphous alloys present a metastable state due to their unique microstructure, long-range disorder and short-range order. This structure gives amorphous alloys a series of excellent soft magnetic properties, such as low coercivity, high magnetic permeability and low loss. Therefore, they are widely used in transformers, motors, switching power supplies and other fields, meeting the requirements of modern industry for high frequency, miniaturization and high efficiency.

[0003] However, in actual production, amorphous alloy strips usually have certain residual stresses after being formed through a rapid cooling process. When these strips are wound into iron cores, new stresses are further introduced. In order for amorphous alloys to exert their best soft magnetic properties, these stresses must be effectively eliminated. Traditionally, this goal is achieved by heat treatment in a vacuum environment, that is, heating and holding the material under conditions not exceeding 773K. However, this method may lead to incomplete stress release due to uneven temperature distribution in the furnace, especially on larger volumes of amorphous alloys, thereby affecting the soft magnetic properties of the material. In addition, if the holding time is set improperly, either the stress cannot be fully removed or crystallization of the material surface may occur, the latter of which will cause the material to break during subsequent processing. To this end, some researchers have tried to improve the temperature uniformity during annealing by adding auxiliary heat sources or improving the design of heat treatment furnaces.

[0004] On the other hand, as electronic technology develops towards higher frequencies and smaller sizes, the requirements for soft magnetic materials are also increasing. Especially under high-frequency conditions, the loss of the core will increase significantly, which is mainly composed of hysteresis loss and eddy current loss. Hysteresis loss is linearly related to frequency, while eddy current loss is proportional to the square of frequency, which means that as the frequency increases, eddy current loss will increase sharply. In order to reduce losses under high-frequency operation, measures need to be taken to reduce eddy current losses. Common practices include thinning the material thickness or enhancing the insulation effect between layers.

[0005] In view of the above analysis, the present invention aims to propose a new method for preparing amorphous iron cores to solve the problem of the decline of soft magnetic properties of conventional amorphous iron cores after annealing and varnishing. By optimizing the heat treatment process and enhancing interlayer insulation, the comprehensive performance of amorphous iron cores can be improved to meet the needs of modern electronic devices for high-performance soft magnetic materials. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an amorphous iron core to solve the technical problems mentioned in the above background technology.

[0007] The technical solution for achieving the purpose of the present invention is: A method for preparing an amorphous iron core comprises the following preparation steps: (1) winding an iron-based amorphous alloy strip to obtain an amorphous iron core blank; (2) pre-annealing the amorphous iron core blank; (3) wrapping a copper strip inside and outside the amorphous iron core blank after the pre-annealing treatment and performing a secondary annealing treatment; (4) placing the amorphous iron core blank after the secondary annealing treatment into an insulating adhesive for vacuum impregnation, taking it out and placing it in an oven for drying to obtain an amorphous iron core.

[0008] Furthermore, the pre-annealing treatment steps are as follows: under nitrogen protection, the amorphous iron core blank is pre-annealed at a first annealing temperature of 375~385°C, and the pre-annealing holding time is 85~95min; a 40mT DC transverse magnetic field is added during the pre-annealing holding process, and a 36mT DC longitudinal magnetic field is added during the cooling process.

[0009] Furthermore, the ratio of the copper strip winding thickness to the thickness of the amorphous iron core blank is 2-4:2.

[0010] Furthermore, the temperature of the secondary annealing treatment is 410-420° C., and the annealing holding time is 14-16 min.

[0011] Furthermore, the insulating adhesive comprises, by weight, 1 to 1.2 parts by weight of an initiator, 128 to 144 parts by weight of a solvent, 59 to 61 parts by weight of tetrafluoroethylene, 5.5 to 5.7 parts by weight of ethylene, 14 to 15 parts by weight of hexafluoropropylene, 101 to 102.2 parts by weight of a silicon-based fluorinated macromonomer, 0.001 to 0.002 parts by weight of nitric acid, 1 to 2 parts by weight of alcohol, 0.1 to 0.2 parts by weight of water, and 1 to 2 parts by weight of ethyl silicate.

[0012] Furthermore, the preparation method of the insulating adhesive is as follows: 5.0 MPa is charged into a high-pressure reactor at room temperature. The nitrogen was exhausted three times to remove the oxygen in the reactor. After vacuuming, 1-1.2 parts by mass of initiator azobisisobutyronitrile and 128-144 parts by mass of solvent 1,1,2-trichloro-1,2,2-trifluoroethane were added to the high-pressure reactor. 59-61 parts by mass of tetrafluoroethylene, 5.5-5.7 parts by mass of ethylene and 14-15 parts by mass of hexafluoropropylene were added. The magnetic stirring was started. After sufficient stirring, the reactor was placed in a 64-66° C. water bath for polymerization reaction for 6-10 hours. 101-102.2 parts by mass of silicon-based fluorinated macromonomer were added to continue the polymerization reaction for 6-10 hours. After the reaction was completed, the reactor was naturally cooled to room temperature, the gas valve was opened to slowly release the unreacted gas monomer, and then mixed with 1-2 parts by mass of alcohol, 0.1-0.2 parts by mass of water, 0.001-0.002 parts by mass of nitric acid and 1-2 parts by mass of ethyl silicate to obtain an insulating adhesive.

[0013] Furthermore, the preparation method of the silicon-based fluorinated macromonomer is as follows: at room temperature, a mixed solution of 8.7 to 8.74 parts by mass of toluene and 8.9 to 9.1 parts by mass of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is added dropwise to a mixture of 2 to 2.2 parts by mass of ethyl silicate, 0.1 to 0.104 parts by mass of tri(pentafluorophenyl)borane and 8.70 to 8.74 parts by mass of toluene, and then stirred at 59 to 61° C. for 11.5 to 12.5 hours. After removing the solvent toluene under reduced pressure, the mixture is purified by silica gel column chromatography using n-hexane as an eluent to obtain a silicon-based fluorinated macromonomer.

[0014] The preparation mechanism of silicon-based fluorinated macromonomers is as follows:

[0015] Furthermore, the vacuum impregnation time is 50-70 min and the pressure is -0.1 MPa.

[0016] By adopting the above technical solution, the present invention has the following beneficial effects: (1) When preparing the amorphous iron core of the present invention, the amorphous iron core blank is firstly subjected to pre-annealing treatment, and then copper strips are wrapped around the inside and outside for secondary annealing treatment, and finally vacuum impregnation is performed with an insulating adhesive. The obtained amorphous iron core has good soft magnetic properties and a smooth surface insulating layer without cracks.

[0017] (2) The present invention performs pre-annealing on the amorphous iron core blank, which can realize the early and slow release of the amorphous latent heat, reduce the crystallization impulse temperature, and initially improve the initial magnetic permeability of the amorphous iron core blank. The hysteresis loop obtained after the pre-annealing treatment by first applying a transverse magnetic field and then a longitudinal magnetic field is similar to the hysteresis loop after the longitudinal magnetic field annealing, which is a rectangular hysteresis loop. The remanence and magnetic permeability of the pre-annealed amorphous iron core blank increase, and the magnetic induction intensity is close to saturation under a magnetic field of less than 100 A / m; at the same time, the advantages of transverse magnetic field annealing are retained: the magnetic domain orientation is perpendicular to the magnetization field direction, so the magnetization process can be regarded as a complete domain rotation process, and its coercive force is significantly lower than that of longitudinal magnetic field annealing, and the loss is significantly lower than that of longitudinal magnetic field annealing; the amorphous alloy iron core obtained by this annealing method has excellent comprehensive performance, high magnetic permeability and low loss.

[0018] (3) When preparing the amorphous iron core of the present invention, copper strips are wrapped inside and outside the amorphous iron core blank after pre-annealing treatment for secondary annealing treatment. The good thermal conductivity of copper is used to enhance heat transfer, which can improve the equivalent thermal conductivity of the material, enhance heat transfer, reduce the temperature difference of the system, and improve the temperature uniformity of the temperature field. After copper is evenly wrapped on the inside and outside of the amorphous iron core, the effective thermal conductivity of the amorphous iron core blank as a whole is improved. Considering that the heat transfer method is heat conduction, the temperature difference of the amorphous iron core blank is reduced, which promotes the uniformity of its internal stress distribution, makes the temperature field more uniform, reduces the difference in coercive force at different positions of the amorphous iron core, and improves the initial magnetic permeability of the amorphous iron core, thereby improving the annealing efficiency and the excellent performance of high magnetic permeability and low loss.

[0019] (4) The insulating adhesive of the present invention uses an initiator, a solvent, tetrafluoroethylene, ethylene, hexafluoropropylene, a silicon-based fluorinated macromonomer, nitric acid, alcohol, water, and ethyl silicate; tetrafluoroethylene, ethylene, hexafluoropropylene, and a silicon-based fluorinated macromonomer are first copolymerized, and then nitric acid, alcohol, water, and ethyl silicate are added to mix, and the molecular chains of the tetrafluoroethylene, ethylene, and hexafluoropropylene copolymer are introduced into the silicon-oxygen polymer, thereby avoiding the problem of agglomeration after the conventional tetrafluoroethylene copolymer is mixed with nano-silicon dioxide, and effectively avoiding the problem of stress on the varnish layer caused by magnetostriction of the iron-based amorphous alloy strip in the amorphous core, resulting in cracking of the varnish layer and affecting the soft magnetic properties of the amorphous core. DETAILED DESCRIPTION

[0021] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0022] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0023] The raw material components of the examples and comparative examples of the present invention are as follows: The preparation method of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is as follows: 173 parts by mass of 4-bromophenol, 152 parts by mass of m-xylene, 770 parts by mass of dimethyl sulfoxide and 670 parts by mass of potassium hydroxide are added to a container equipped with a Dean-Stark device, a condenser, a thermometer and a mechanical stirrer, and the mixture is stirred and heated to 80° C. and stirred continuously until the potassium hydroxide is dissolved, and the pressure is reduced to 15 mmHg, and the m-xylene / water azeotrope is removed by distillation, and the mixture is ... mixture is stirred continuously at 80° C. Continue heating for 80 hours to allow the system to reach atmospheric pressure, then cool to 30°C, replace the Dean-Stark apparatus and condenser with an additional funnel containing 286.0 parts by mass of 1,2-dibromotetrafluoroethane, slowly add dibromotetrafluoroethane in a 25°C water bath over 2 hours, then stir at room temperature for 3 hours, continue heating to 50°C for 14 hours, then add distilled water, and after separation, wash the organic phase with 500 parts by mass of 5% sodium carbonate solution and 500 parts by mass of distilled water. , and then distill the light brown liquid to obtain intermediate 1; 50 parts by mass of active zinc are suspended in 380 parts by mass of acetonitrile, and then 215.0 parts by mass of intermediate 1 are added within 1 hour, mixed and heated under reflux for 16 hours, and then cooled to room temperature, acetonitrile is removed by evaporation under reduced pressure, 1400 parts by mass of hexane are added for extraction, and then distilled under reduced pressure for separation and concentration to obtain intermediate 2; under stirring conditions, 6.34 parts by mass of 50 mesh magnesium powder and 0.001 parts by mass of Iodine, 45.00 parts by mass of chlorodimethylsilane and 320 parts by mass of tetrahydrofuran were mixed at room temperature, and then 60.00 parts by mass of intermediate 2 were added and mixed. After the mixture began to release heat and darkened, it was cooled to 0-5°C with an ice bath. After the addition was completed, it was slowly heated to room temperature within 5 hours, and after stirring at room temperature for 15 hours, the reaction was quenched with 25 parts by mass of water and 200 parts by mass of hexane, filtered through silica gel, and distilled and concentrated under reduced pressure to obtain 4-[trifluorovinyl (oxy) phenyl] dimethylsilane.

[0024] The preparation mechanism of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is as follows:

[0025] The material of the iron-based amorphous alloy strip includes Fe 73.5 Si 13.5 B9Cu1Nb2V1、Fe 80 SiC 11 , Fe 80 Co3Si3B 10 Any one of P1C3; the preferred material of the iron-based amorphous alloy strip in the embodiments of the present invention and the comparative examples is Fe 80 SiC 11 ; The thickness of the iron-based amorphous alloy strip is 26μm and the width is 10mm. Example 1

[0026] A method for preparing an amorphous iron core comprises the following steps: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 24.5 mm and the outer diameter is 35 mm; (2) Pre-annealing the amorphous iron core blank: Under nitrogen protection, pre-anneal the amorphous iron core blank at a first annealing temperature of 375°C, with a pre-annealing holding time of 85 minutes and a temperature rise rate of 6.5°C / min; a 40mT DC transverse magnetic field is applied during the pre-annealing holding process, and a 36mT DC longitudinal magnetic field is applied during the cooling process; (3) After the pre-annealing treatment, the amorphous iron core blank is wrapped with copper tape inside and outside, and the ratio of the copper tape thickness to the thickness of the amorphous iron core blank is 2:2. Then, a secondary annealing treatment is performed under nitrogen protection. The secondary annealing treatment temperature is 410°C and the annealing holding time is 14 minutes. (4) The amorphous iron core blank after the secondary annealing treatment is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour before being taken out, placed in a 120°C oven for drying, and then heated to 250°C and kept at this temperature for 30 seconds. Finally, the blank is cooled in the oven to room temperature and taken out to obtain an amorphous iron core.

[0027] The preparation method of the insulating adhesive is as follows: filling a high-pressure reactor with 5.0 MPa nitrogen gas and exhausting it three times at room temperature to remove oxygen in the reactor, adding 1 part by mass of initiator azobisisobutyronitrile and 128 parts by mass of solvent 1,1,2-trichloro-1,2,2-trifluoroethane to the high-pressure reactor after vacuuming, adding 59 parts by mass of tetrafluoroethylene, 5.5 parts by mass of ethylene, and 14 parts by mass of hexafluoropropylene as gas monomers, starting magnetic stirring, and placing the reactor in a 64° C. water bath for polymerization reaction for 6 hours after sufficient stirring, adding 101 parts by mass of silicon-based fluorinated macromonomers and continuing the polymerization reaction for 6 hours, and after the reaction is completed, naturally cooling the reactor to room temperature, opening the gas valve to slowly release the unreacted gas monomers, and then mixing with 1 part by mass of alcohol, 0.1 part by mass of water, 0.001 part by mass of nitric acid, and 1 part by mass of ethyl silicate to obtain the insulating adhesive.

[0028] The preparation method of the silicon-based fluorinated macromonomer is as follows: at room temperature, a mixed solution of 8.7 parts by mass of toluene and 8.9 parts by mass of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is added dropwise to a mixture of 2 parts by mass of ethyl silicate, 0.1 parts by mass of tri(pentafluorophenyl)borane and 8.70 parts by mass of toluene, and then stirred at 59° C. for 11.5 hours. After removing the solvent toluene under reduced pressure, the mixture is purified by silica gel column chromatography using n-hexane as an eluent to obtain a silicon-based fluorinated macromonomer. Example 2

[0029] A method for preparing an amorphous iron core comprises the following steps: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) Pre-annealing the amorphous iron core blank: Under nitrogen protection, pre-anneal the amorphous iron core blank at a first annealing temperature of 380°C, with a pre-annealing holding time of 90 minutes and a temperature rise rate of 6.5°C / min; a 40mT DC transverse magnetic field is applied during the pre-annealing holding process, and a 36mT DC longitudinal magnetic field is applied during the cooling process; (3) After the pre-annealing treatment, the amorphous iron core blank is wrapped with copper tape inside and outside, and the ratio of the copper tape thickness to the amorphous iron core blank thickness is 3:2. Then, a secondary annealing treatment is performed under nitrogen protection. The secondary annealing treatment temperature is 415°C and the annealing holding time is 15 minutes. (4) The amorphous iron core blank after secondary annealing is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, and then heated to 260°C for 30 seconds, and finally taken out after cooling to room temperature in the oven to obtain an amorphous iron core.

[0030] The preparation method of the insulating adhesive is as follows: filling a high-pressure reactor with 5.0 MPa nitrogen gas and exhausting it three times at room temperature to remove oxygen in the reactor, adding 1.1 parts by mass of initiator azobisisobutyronitrile and 136 parts by mass of solvent 1,1,2-trichloro-1,2,2-trifluoroethane to the high-pressure reactor after vacuuming, adding 60 parts by mass of tetrafluoroethylene, 5.6 parts by mass of ethylene, and 14.5 parts by mass of hexafluoropropylene as gas monomers, starting magnetic stirring, placing the reactor in a 65° C. water bath for polymerization reaction for 8 hours after sufficient stirring, adding 101.6 parts by mass of silicon-based fluorinated macromonomers and continuing the polymerization reaction for 8 hours, and after the reaction is completed, naturally cooling the reactor to room temperature, opening the gas valve to slowly release the unreacted gas monomers, and then mixing with 1.5 parts by mass of alcohol, 0.15 parts by mass of water, 0.0015 parts by mass of nitric acid, and 1.5 parts by mass of ethyl silicate to obtain the insulating adhesive.

[0031] The preparation method of the silicon-based fluorinated macromonomer is as follows: at room temperature, a mixed solution of 8.72 parts by mass of toluene and 9 parts by mass of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is added dropwise to a mixture of 2.1 parts by mass of ethyl silicate, 0.102 parts by mass of tri(pentafluorophenyl)borane and 8.72 parts by mass of toluene, and then stirred at 60° C. for 12 hours. After removing the solvent toluene under reduced pressure, the mixture is purified by silica gel column chromatography using n-hexane as an eluent to obtain a silicon-based fluorinated macromonomer. Example 3

[0032] A method for preparing an amorphous iron core comprises the following steps: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25.5 mm and the outer diameter is 35.5 mm; (2) Pre-annealing the amorphous iron core blank: Under nitrogen protection, pre-anneal the amorphous iron core blank at a first annealing temperature of 385°C, with a pre-annealing holding time of 95 minutes and a temperature rise rate of 6.5°C / min; a 40mT DC transverse magnetic field is applied during the pre-annealing holding process, and a 36mT DC longitudinal magnetic field is applied during the cooling process; (3) After the pre-annealing treatment, the amorphous iron core blank is wrapped with copper tape inside and outside, and the ratio of the copper tape thickness to the thickness of the amorphous iron core blank is 4:2. Then, a secondary annealing treatment is performed under nitrogen protection. The temperature of the secondary annealing treatment is 420°C, and the annealing holding time is 16 minutes; (4) The amorphous iron core blank after secondary annealing is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, and then heated to 270°C for 30 seconds. Finally, the blank is cooled in the oven to room temperature and taken out to obtain an amorphous iron core.

[0033] The preparation method of the insulating adhesive is as follows: filling a high-pressure reactor with 5.0MPa nitrogen gas and exhausting it three times at room temperature to remove oxygen in the reactor, adding 1.2 parts by mass of initiator azobisisobutyronitrile and 128-144 parts by mass of solvent 1,1,2-trichloro-1,2,2-trifluoroethane to the high-pressure reactor after vacuuming, adding 61 parts by mass of tetrafluoroethylene, 5.7 parts by mass of ethylene, and 15 parts by mass of hexafluoropropylene as gas monomers, starting magnetic stirring, and placing the reactor in a 66°C water bath for polymerization reaction for 10 hours after sufficient stirring, adding 102.2 parts by mass of silicon-based fluorinated macromonomers to continue polymerization reaction for 10 hours, and after the reaction is completed, naturally cooling the reactor to room temperature, opening the gas valve to slowly release the unreacted gas monomers, and then mixing with 2 parts by mass of alcohol, 0.2 parts by mass of water, 0.002 parts by mass of nitric acid, and 2 parts by mass of ethyl silicate to obtain the insulating adhesive.

[0034] The preparation method of the silicon-based fluorinated macromonomer is as follows: at room temperature, a mixed solution of 8.74 parts by mass of toluene and 9.1 parts by mass of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is added dropwise to a mixture of 2.2 parts by mass of ethyl silicate, 0.104 parts by mass of tri(pentafluorophenyl)borane and 8.74 parts by mass of toluene, and then stirred at 61° C. for 12.5 hours. After removing the solvent toluene under reduced pressure, the mixture is purified by silica gel column chromatography using n-hexane as an eluent to obtain a silicon-based fluorinated macromonomer.

[0035] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is step (2): pre-annealing the amorphous iron core blank: under nitrogen protection, pre-annealing the amorphous iron core blank at a first annealing temperature of 380° C., and the pre-annealing holding time is 90 min; the remaining components and steps are the same as in Example 2.

[0036] Comparative Example 2 The difference between Comparative Example 2 and Example 2 lies in the steps of preparing the amorphous core: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) Copper tape is wound inside and outside the amorphous iron core blank, and the ratio of the copper tape winding thickness to the amorphous iron core blank thickness is 3:2, followed by secondary annealing treatment under nitrogen protection, the secondary annealing treatment temperature is 415°C, and the annealing holding time is 15 min; (3) The amorphous iron core blank after the secondary annealing treatment is immersed in an insulating adhesive, and then placed in a vacuum impregnation device and evacuated to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, and then heated to 260°C for 30 seconds, and finally cooled to room temperature in the oven and taken out to obtain an amorphous iron core; the remaining components and steps are the same as those in Example 2.

[0037] Comparative Example 3 The difference between Comparative Example 3 and Example 2 lies in the steps of preparing the amorphous core: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) Pre-annealing the amorphous iron core blank: pre-annealing the amorphous iron core blank at a first annealing temperature of 380° C. under nitrogen protection, with a pre-annealing holding time of 90 min; a 40 mT DC transverse magnetic field is applied during the pre-annealing holding process, and a 36 mT DC longitudinal magnetic field is applied during the cooling process; (3) The amorphous iron core blank after pre-annealing treatment is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, heated to 260°C for 30 seconds, and finally taken out with the oven cooled to room temperature to obtain an amorphous iron core; the remaining components and steps are the same as in Example 2.

[0038] Comparative Example 4 The difference between Comparative Example 4 and Example 2 lies in the steps of preparing the amorphous core: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) annealing the amorphous iron core blank at 380° C. under nitrogen protection for 90 min; applying a 40 mT DC transverse magnetic field during the pre-annealing, and applying a 36 mT DC longitudinal magnetic field during the cooling process; (3) The annealed amorphous iron core blank is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, heated to 260°C for 30 seconds, and finally taken out after cooling to room temperature in the oven to obtain an amorphous iron core; the remaining components and steps are the same as those in Example 2.

[0039] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies in the steps of preparing the amorphous core: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) Under nitrogen protection, the amorphous iron core billet is annealed at 415°C for 90 minutes; (3) The annealed amorphous iron core blank is immersed in an insulating adhesive, then placed in a vacuum impregnation device and pumped to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, heated to 260°C for 30 seconds, and finally taken out after cooling to room temperature in the oven to obtain an amorphous iron core; the remaining components and steps are the same as those in Example 2.

[0040] Comparative Example 6 The difference between Comparative Example 6 and Example 2 lies in the steps of preparing the amorphous core: (1) Winding the iron-based amorphous alloy strip to obtain an amorphous iron core blank, wherein the inner diameter of the amorphous iron core blank is 25 mm and the outer diameter is 35.3 mm; (2) Pre-annealing the amorphous iron core blank: pre-annealing the amorphous iron core blank at a first annealing temperature of 380° C. under nitrogen protection, with a pre-annealing holding time of 90 min; a 40 mT DC transverse magnetic field is applied during the pre-annealing holding process, and a 36 mT DC longitudinal magnetic field is applied during the cooling process; (3) After the pre-annealing treatment, the amorphous iron core blank is subjected to secondary annealing treatment, the temperature of the secondary annealing treatment is 415°C, and the annealing holding time is 15 minutes; (4) The amorphous iron core blank after the secondary annealing treatment is immersed in an insulating adhesive, and then placed in a vacuum impregnation device and evacuated to -0.1 MPa for 1 hour, then taken out, placed in a 120°C oven for drying, and then heated to 260°C for 30 seconds, and finally cooled to room temperature in the oven and taken out to obtain an amorphous iron core; the remaining components and steps are the same as those in Example 2.

[0041] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that the preparation method of the insulating adhesive is: mixing 7.999 parts by mass of ethyl orthosilicate, 88 parts by mass of alcohol, 4 parts by mass of deionized water and 0.001 parts by mass of nitric acid; the remaining components and steps are the same as those in Example 2.

[0042] Comparative Example 8 The difference between Comparative Example 8 and Example 2 is that the main components of the insulating adhesive are 100 parts by mass of tetrafluoroethylene-hexafluoropropylene copolymer and 10 parts by mass of silicon dioxide; the remaining components and steps are the same as those of Example 2.

[0043] Effect example Surface appearance: Observe the surface morphology of the amorphous cores prepared in the examples and comparative examples.

[0044] The MATS-2010SD soft magnetic DC measuring device produced by Hunan Lianzhong was used to measure the DC magnetic properties of the amorphous cores prepared in the embodiments and comparative examples; The AC loss of the amorphous cores prepared in the embodiments and comparative examples was measured using an IWATSU SY8232B-H analyzer produced by Iwasaki, Japan.

[0045] Appearance <![CDATA[Core loss P 1000Hz,1T (W / kg)]]> <![CDATA[Initial permeability μ i (10 4 Ge / Oe)]]> Standard deviation of coercivity at different positions Example 1 No particles, no cracks 2.9 13.16 0.0704 Example 2 No particles, no cracks 2.3 13.24 0.0689 Example 3 No particles, no cracks 2.6 13.18 0.0711 Comparative Example 1 No particles, no cracks 3.2 12.21 0.0706 Comparative Example 2 No particles, no cracks 4.0 6.86 0.0710 Comparative Example 3 No particles, no cracks 3.1 10.23 0.1992 Comparative Example 4 No particles, no cracks 4.4 3.02 0.1989 Comparative Example 5 No particles, no cracks 4.2 3.88 0.1994 Comparative Example 6 No particles, no cracks 3.9 11.63 0.1990 Comparative Example 7 Lots of cracks 7.3 12.23 0.0706 Comparative Example 8 Lots of pellets, no cracks 4.8 12.26 0.0709 According to the comparison of the experimental data of the embodiment and the comparative example in the above table, the amorphous core prepared in the embodiment has better appearance, lower loss at a frequency of 1kHz and a Bm of 1T, and smaller difference in coercive force; Comparative Example 1 is a pre-annealing process in which a 40mT DC transverse magnetic field is not added, and a 36mT DC longitudinal magnetic field is added during the cooling process. Compared with the comparative example 1, the amorphous iron core of Example 2 has a higher initial permeability and lower loss. This is because the hysteresis loop obtained after the pre-annealing treatment by first adding a transverse magnetic field and then adding a longitudinal magnetic field is similar to the hysteresis loop after the longitudinal magnetic field annealing, which is a rectangular hysteresis loop. The remanence and permeability of the pre-annealed amorphous iron core blank are increased, and the advantages of the transverse magnetic field annealing are retained: the magnetic domain orientation is perpendicular to the magnetization field direction, so the magnetization process can be regarded as a complete domain rotation process, and the loss is low. Comparative Example 2 does not have a pre-annealing process, and only copper-clad annealing is performed. Compared with the amorphous core of Example 2, the pre-annealing process is adopted, and the amorphous latent heat can be released in advance and slowly, thereby reducing the crystallization impulse temperature, and improving the initial magnetic permeability of the amorphous core blank. At the same time, since the hysteresis loop obtained after annealing with a transverse magnetic field first and then a longitudinal magnetic field during the pre-annealing treatment is similar to the hysteresis loop after annealing with a longitudinal magnetic field, which is a rectangular hysteresis loop, the remanence and magnetic permeability of the pre-annealed amorphous core blank are increased, and the advantages of transverse magnetic field annealing are retained: the magnetic domain orientation is perpendicular to the magnetization field direction, so the magnetization process can be regarded as a complete domain rotation process, and the loss is relatively low; Comparative Example 3 is provided with a pre-annealing process, and copper cladding annealing is not performed, and only secondary annealing is performed. Compared with the amorphous core of Example 2, the pre-annealing process is adopted, and the amorphous latent heat can be released in advance and slowly, thereby reducing the crystallization impulse temperature, so that the initial magnetic permeability of the amorphous core blank is improved, the loss is low, and the coercive force difference is small; Comparative Examples 4 and 5 were only annealed and varnished. Compared with the amorphous core of Example 2, the initial magnetic permeability was improved, the loss was lower, and the coercive force difference was smaller; Comparative Example 6 is annealed only with reference to the pre-annealing process, that is, the transverse magnetic field is first added and then the longitudinal magnetic field is added during the annealing process, and copper cladding annealing is not performed. Compared with the amorphous core of Example 2, the initial magnetic permeability is improved, the loss is lower, and the coercive force difference is smaller. This is because the good thermal conductivity of copper is used to enhance heat transfer, which can improve the equivalent thermal conductivity of the material, enhance heat transfer, reduce the temperature difference of the system, and improve the temperature uniformity of the temperature field, thereby reducing the temperature difference of the amorphous core blank, promoting the uniformity of its internal stress distribution, making the temperature field more uniform, reducing the coercive force difference at different positions of the amorphous core, and improving the initial magnetic permeability of the amorphous core, thereby improving the annealing efficiency and the excellent performance of high magnetic permeability and low loss; Comparative Examples 7 and 8 respectively use an insulating binder prepared from tetrafluoroethylene-hexafluoropropylene copolymer and an insulating binder prepared from a mixture of tetrafluoroethylene-hexafluoropropylene copolymer and silicon dioxide. Compared with them, the amorphous core of Example 2 has a better surface morphology and low loss. In addition, the insulating binder obtained by the copolymer of silicon-based fluorinated macromonomer and tetrafluoroethylene, ethylene and hexafluoropropylene introduces high-toughness tetrafluoroethylene, ethylene and hexafluoropropylene copolymer molecular chains into the rigid polysiloxane network to form a branched polymer network with good tensile strength, which can effectively improve and avoid the problem of agglomeration after the conventional tetrafluoroethylene copolymer is mixed with nano-silicon dioxide, and effectively avoid the problem of stress on the varnish layer caused by magnetostriction of the iron-based amorphous alloy strip in the amorphous core, resulting in cracking of the varnish layer and affecting the soft magnetic properties of the amorphous core.

[0046] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an amorphous iron core, characterized in that: The method comprises the following preparation steps: (1) winding an iron-based amorphous alloy strip to obtain an amorphous iron core blank; (2) pre-annealing the amorphous iron core blank; (3) wrapping a copper strip inside and outside the amorphous iron core blank after the pre-annealing treatment to perform a secondary annealing treatment; and (4) placing the amorphous iron core blank after the secondary annealing treatment into an insulating adhesive for vacuum impregnation, taking it out and placing it into an oven for drying to obtain an amorphous iron core.

2. The method for preparing an amorphous iron core according to claim 1, characterized in that: The pre-annealing treatment steps are as follows: under nitrogen protection, the amorphous iron core blank is pre-annealed at a first annealing temperature of 375-385°C, and the pre-annealing holding time is 85-95 minutes; a 40mT DC transverse magnetic field is added during the pre-annealing holding process, and a 36mT DC longitudinal magnetic field is added during the cooling process.

3. The method for preparing an amorphous iron core according to claim 1, characterized in that: The ratio of the copper strip winding thickness to the amorphous iron core blank thickness is 2-4:

2.

4. The method for preparing an amorphous iron core according to claim 1, characterized in that: The temperature of the secondary annealing treatment is 410-420° C., and the annealing holding time is 14-16 minutes.

5. The method for preparing an amorphous iron core according to claim 1, characterized in that: The insulating adhesive comprises, by weight, 1-1.2 parts of initiator, 128-144 parts of solvent, 59-61 parts of tetrafluoroethylene, 5.5-5.7 parts of ethylene, 14-15 parts of hexafluoropropylene, 101-102.2 parts of silicon-based fluorinated macromonomer, 0.001-0.002 parts of nitric acid, 1-2 parts of alcohol, 0.1-0.2 parts of water and 1-2 parts of ethyl silicate.

6. The method for preparing an amorphous iron core according to claim 1, characterized in that: The preparation method of the insulating adhesive is as follows: fill a high-pressure reactor with 5.0 MPa The nitrogen was exhausted three times to remove the oxygen in the reactor. After vacuuming, 1-1.2 parts by mass of initiator azobisisobutyronitrile and 128-144 parts by mass of solvent 1,1,2-trichloro-1,2,2-trifluoroethane were added to the high-pressure reactor. 59-61 parts by mass of tetrafluoroethylene, 5.5-5.7 parts by mass of ethylene and 14-15 parts by mass of hexafluoropropylene were added. The magnetic stirring was started. After sufficient stirring, the reactor was placed in a 64-66° C. water bath for polymerization reaction for 6-10 hours. 101-102.2 parts by mass of silicon-based fluorinated macromonomer were added to continue the polymerization reaction for 6-10 hours. After the reaction was completed, the reactor was naturally cooled to room temperature, the gas valve was opened to slowly release the unreacted gas monomer, and then mixed with 1-2 parts by mass of alcohol, 0.1-0.2 parts by mass of water, 0.001-0.002 parts by mass of nitric acid and 1-2 parts by mass of ethyl silicate to obtain an insulating adhesive.

7. The method for preparing an amorphous iron core according to claim 6, characterized in that: The preparation method of the silicon-based fluorinated macromonomer is as follows: at room temperature, a mixed solution of 8.7-8.74 parts by mass of toluene and 8.9-9.1 parts by mass of 4-[trifluorovinyl(oxy)phenyl]dimethylsilane is added dropwise to a mixture of 2-2.2 parts by mass of ethyl silicate, 0.1-0.104 parts by mass of tri(pentafluorophenyl)borane and 8.70-8.74 parts by mass of toluene, and then stirred at 59-61° C. for 11.5-12.5 hours, and after removing the solvent toluene under reduced pressure, the mixture is purified by silica gel column chromatography using n-hexane as an eluent to obtain the silicon-based fluorinated macromonomer.

8. The method for preparing an amorphous iron core according to claim 6, characterized in that: The vacuum impregnation time is 50-70 minutes, and the pressure is -0.1 MPa.